Critique of Total Quality Management in Islamic Education: Proposing Prophetic Leadership as a Model for Quality Enhancement - Dinata, Yuriyan; Andriani, Tuti (Journal of Islamic Education and Ethics, 2025)
Total Quality Management (TQM) has been widely implemented in educational institutions to enhance quality through efficiency, productivity, and standardization. However, its application within Islamic education contexts presents epistemological and pedagogical tensions, particularly due to TQM’s roots in industrial and materialistic rationality, which may not fully align with Islamic education's holistic and spiritual aims. This study critically examined these tensions and proposes prophetic leadership as a conceptual alternative. The research analyzed the conceptual underpinnings of TQM, Islamic education, and prophetic leadership using a literature review and a descriptive-critical approach. The findings suggested that TQM often overlooks the spiritual and moral dimensions of learning, tends to homogenize student development, and orients educational processes toward market-driven outcomes. In contrast, prophetic leadership—grounded in values such as siddiq, amanah, tabligh, and fathanah—offers a more integrative framework that embraces intellectual, emotional, and spiritual development. This model resonates more closely with the foundational goals of Islamic education by promoting balance between worldly and transcendental aims and responding to the challenges of postmodern society. This study recommends integrating prophetic leadership values into Islamic educational policy design and teacher training programs. It suggests future empirical research to test the applicability and impact of this model across various Islamic schooling contexts.